ANALYSIS OF THE EPIDEMIOLOGICAL FEATURES OF DIARRHEAL DISEASES IN CHILDREN IN THE SOUTHERN ARAL REGION (Multidisciplinary Journal of Science and Technology, 2024)
Despite the downward trend, the incidence of diarrheal diseases in the Republic of Uzbekistan remains at high levels, which emphasizes the relevance of this problem for our country. The high incidence of diarrheal diseases among the child population, a severe course, especially in early childhood, which determine the mortality rates for this pathology, determines the study of the prevalence, level, structure of incidence, etiological structure, dynamics of detection of infectious agents.